(untitled) (Journal Of Educational and Psychological Researches, 2022)
This current research aims to reveal the difference between the levels of teaching expertise of physics teachers according to the years of service by answering the following question: does the educational skill level of physics teachers work according to the service? The sample of the study consisted of (225) physics teachers by (125) females (56%), and (100) males (44%), distributed on (4) education directorates in Baghdad governorate on both sides of al-Karkh and al-Rusafa. In order to achieve the aim of the study, the researcher prepared a note card for expertise teaching, consisting of (39) paragraphs distributed into (5) fields. The apparent validity and reliability of the card were verified through an agreement (the researcher herself) and the researcher with two others. The following statistical methods were used (Pearson Correlation Coefficient, mean, Cooper’s Equation). The results indicated that the expertise teaching of the high school physics teachers was at a good level (71.3%). The researcher offered a set of recommendations and suggestions.